2020
DOI: 10.1155/2020/8749764
|View full text |Cite
|
Sign up to set email alerts
|

Development of an IoT-Based Indoor Air Quality Monitoring Platform

Abstract: In this paper, an IoT-based indoor air quality monitoring platform, consisting of an air quality-sensing device called “Smart-Air” and a web server, is demonstrated. This platform relies on an IoT and a cloud computing technology to monitor indoor air quality in anywhere and anytime. Smart-Air has been developed based on the IoT technology to efficiently monitor the air quality and transmit the data to a web server via LTE in real time. The device is composed of a microcontroller, pollutant detection sensors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(67 citation statements)
references
References 28 publications
1
65
0
1
Order By: Relevance
“…Recently, smart devices based on the integration of cloud computing and IoT have been developed to precisely monitor IAQ and efficiently transmit real-time data to a cloud computing-based web server using an IoT sensor network [182,183]. Jo et al (2020) introduced a Smart-Air device to collect reliable and accurate data for IAQ monitoring ( Figure 4C) [184]. The Smart-Air device includes three components: A pollutant detection sensor array, a microcontroller, and an LTE modem.…”
Section: Internet Of Thing (Iot)-based Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, smart devices based on the integration of cloud computing and IoT have been developed to precisely monitor IAQ and efficiently transmit real-time data to a cloud computing-based web server using an IoT sensor network [182,183]. Jo et al (2020) introduced a Smart-Air device to collect reliable and accurate data for IAQ monitoring ( Figure 4C) [184]. The Smart-Air device includes three components: A pollutant detection sensor array, a microcontroller, and an LTE modem.…”
Section: Internet Of Thing (Iot)-based Systemsmentioning
confidence: 99%
“…Importantly, the Korean Ministry of Environment testing has demonstrated that the device is highly reliable. All received data is stored in the web server's cloud to provide resources for further analysis of IAQ [184]. According to the concept of the combination of ventilation system activation with IAQ-variable-level detection, a strategy for IAP reduction by demand-controlled ventilation systems (DCVs) based on CO 2 detection was recently developed [185].…”
Section: Internet Of Thing (Iot)-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several previous studies, systems based on LCSSs providing real-time data of air pollution were designed and implemented. Monitoring units proposed in [23,[30][31][32][33] are devoted to indoor air quality monitoring. The system illustrated in [23] was designed to compute an Indoor Environment Quality index (IEQ).…”
Section: Introductionmentioning
confidence: 99%
“…There are some proposals for indoor monitoring as in [12], an indoor air quality monitoring platform based on IoT technology was developed. It consists of an air quality-sensing device and a web server on cloud computing to monitor indoor air quality.…”
Section: Current Context Of the Air Quality Monitoring Platformsmentioning
confidence: 99%